A búcsúztató kiadványok szerepe a 16. századi egyetemjárásban - Móré, Tünde (Gerundium, 2016)
THE ROLE OF SCHOOL-LEAVING DOCUMENTATION IN THE UNIVERSITY ATTENDANCE OF 16TH CENTURY INSTITUTIONS. Hungarian students in the 16th century, especially those attending the University of Wittenberg, were challenged by a continually multiplying textual universe which was based on the multi-level imitation of the ancient authors, and which created diferent varieties of imitation from time to time. In the universities, the community of respublica litteraria was made up of professors, their families and also of students. Regarding this particular community, a variety of features surfaced: the development of ‘sodalitates’, letter writing, the humanistic friendship, the knowledge of Latin, or the use of Latin names. he paper highlights the nature of the relationships the Hungarian student group sustained with this imagined community, which was oicially founded in Wittenberg, 1555.